Construction of Religious Habitus In Indonesian Islamic Boarding Schools - Taufiq, Amal; Sahdan, Mohd Zainizan; Setianingsih, Dwi (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
Islamic boarding schools are Islamic educational institutions in Indonesia that are unique among other educational institutions and have a strong religious habitus. This research aims to find out what the religious habitus of Islamic boarding schools looks like and what the construction process of religious habitus is in the Al-Islam Islamic boarding school in Ponorogo, East Java. Qualitative methods were used in this research, including observation, interview, and documentation techniques, as tools for collecting data. This research shows that the habitus characteristics of the Al-Islam Islamic boarding school include three aspects. Firstly, hysteresis lasts long and is not easily changed; it is difficult to change once formed. Secondly, transposability can be inherited and can be learned. Thirdly, it is a generator that encourages the growth of new social practices. The construction of the habitus of the Al-Islam Islamic boarding school at the beginning of its establishment went through a long dialectical process by the founders of the Islamic boarding school. Then, it was instilled in the students in various ways, including in the curriculum, role models from Kyai (the head of Islamic boarding schools), and instilling the Islamic boarding school’s philosophy of the five souls. The results of this research can contribute to strengthening religious habitus in Islamic boarding schools as religious education institutions regarding the importance of role models and a conducive environment in forming the religious habitus of students.